Música, estética e sociedade nos escrito de Jorge Peixinho - Teixeira, Cristina Delgado 1964- (Lisbon Colibri Centro de Estudos de Sociologia e Estética Musical, 2006)
Composer Jorge Peixinho has always cultivated a personal reflection on his own work and his musical career. A committed musician, he remained attentive to the cultural dynamics and aesthetic debates that characterised the second half of the 20th century. This book offers a contextualised reading of Jorge Peixinho's place in these debates and dynamics, based on his writings and interviews. In the first part, we follow the trail of his critical-pedagogical discourse on Portuguese musical life, a journey that allows us to discover Jorge Peixinho's awareness of his social role and his historical place as a composer, pedagogue, music critic and performer. The second part offers a perspective on Peixinho's reading of Western music and his own music, integrating his thinking and his work into the debates surrounding the avant-garde and postmodern aesthetics. (Translated with DeepL.com)
Keywords: Peixinho, Jorge -- 1940-1995; Music history; Music philosophy and esthetics; Composer